2018
DOI: 10.1021/acs.jafc.7b05807
|View full text |Cite
|
Sign up to set email alerts
|

Honeydew Honeys: A Review on the Characterization and Authentication of Botanical and Geographical Origins

Abstract: The commercial interest in honeydew honeys (from the secretions of plants or the excretions of plant-sucking insects found on plants) is increasing because of their higher therapeutic properties compared with those of most blossom honeys (from nectar). However, honeydew honeys have been less studied than blossom honeys. In this work, studies carried out to characterize and authenticate honeydew honeys by their botanical and geographical origins have been reviewed. The identification of honey origins has been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 82 publications
(232 reference statements)
0
57
0
3
Order By: Relevance
“…Moreover, botanical origin of honey could be successfully determined by electrical conductivity, among the other physicochemical parameters. 3,13 Considering the results of sugar content, only negligible extent content of melezitose indicate differences between samples, while other studies suggested considerable lower levels of monosaccharides, 13 and higher levels of oligosaccharides 6,7 in honeydew honey. Great similarity of physicochemical parameters for two types of honey types originating from a small geographical region indicates that honeydew honeys and poly-oral honeys represent a complex mixture of honeydew and nectar from different botanical species.…”
Section: Physicochemical Analysismentioning
confidence: 78%
See 2 more Smart Citations
“…Moreover, botanical origin of honey could be successfully determined by electrical conductivity, among the other physicochemical parameters. 3,13 Considering the results of sugar content, only negligible extent content of melezitose indicate differences between samples, while other studies suggested considerable lower levels of monosaccharides, 13 and higher levels of oligosaccharides 6,7 in honeydew honey. Great similarity of physicochemical parameters for two types of honey types originating from a small geographical region indicates that honeydew honeys and poly-oral honeys represent a complex mixture of honeydew and nectar from different botanical species.…”
Section: Physicochemical Analysismentioning
confidence: 78%
“…Based on the electrical conductivity of the 28 honey samples, eight samples belong to the group of honeydew honey, marked as No. 1,3,4,7,8,16,25,26 (Fig. 1).…”
Section: Honey Classicationmentioning
confidence: 95%
See 1 more Smart Citation
“…These ones are preferred by consumers due to their organoleptic properties and health benefits, being more expensive than the multifloral ones (Silva et al., ). Moreover, physicochemical parameters also allow discrimination between nectar honey and honeydew (Pita‐Calvo & Vázquez, ). Relative to mineral and phenolic contents, their contribution in distinguishing honey is low; however, these are considered environmental markers and influence its nutritional value (Silva et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Their authentication, based on the geographical and botanical origins, has been assuming great importance, being mainly associated with high-quality honeys. The focus is on the analysis of physicochemical parameters, such as pH, moisture, hydroxymethylfurfural (HMF) content, electrical conductivity, sugar and protein measurements, melissopalynology, and target parameters (phenolic compounds, sugars, organic acids, proteins, minerals, DNA markers, among others; Belay, Solomon, Bultossa, Adgaba, & Melaku, 2013;Pita-Calvo & Vázquez, 2013). JFDS-2019-1677Submitted 10/12/2019, Accepted 11/28/2019 Direct inquiries to authors Silva and Alves (Email: luisfarmacognosia@gmail.com; gilberto@fcsaude.ubi.pt). of multifloral honeys.…”
Section: Introductionmentioning
confidence: 99%